2014
DOI: 10.3109/10641963.2014.881847
|View full text |Cite
|
Sign up to set email alerts
|

Association of meteorological factors and seasonality with preeclampsia: a 5-year study in northeast of Iran

Abstract: Seasonal (monthly) variations of the weather (humidity and temperature) have a significant impression on preeclampsia prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Anecdotal evidence, 12 and the delightfully titled article ‘Kilimanjaro, epistaxis and all that’, 13 suggest an increased risk of mucosal surface bleeding at higher altitudes and with lower atmospheric humidity. Recent papers investigating the effect of atmospheric conditions on haemostasis and bleeding in conditions varying from intracerebral haemorrhage 14 and aneurysmal subarachnoid haemorrhage 15 to pre-eclampsia 16 and angina pectoris 17 suggest a significant influence of atmospheric conditions on the incidence of a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal evidence, 12 and the delightfully titled article ‘Kilimanjaro, epistaxis and all that’, 13 suggest an increased risk of mucosal surface bleeding at higher altitudes and with lower atmospheric humidity. Recent papers investigating the effect of atmospheric conditions on haemostasis and bleeding in conditions varying from intracerebral haemorrhage 14 and aneurysmal subarachnoid haemorrhage 15 to pre-eclampsia 16 and angina pectoris 17 suggest a significant influence of atmospheric conditions on the incidence of a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this a 36-month research on 11,958 newborns in Mississippi, found no association between the incidence of hypertension in pregnancy and seasonal variation [ 69 ]. However, a study from the northeast of Iran found a significant association between monthly temperature changes and preeclampsia prevalence; and the highest prevalence of preeclampsia was seen in summer, especially in September (11.1 %) and August (10.3 %) and the lowest prevalence was seen in winter and early spring, especially in January (5.6 %) and April (5.7 %) [ 70 ]. Tam et al, conducted a study in Hong Kong, between 1995 and 2002, and found that women who were pregnant in the summer and had been exposed to higher temperatures were more likely to have preeclampsia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women, especially during late gestation, are much more vulnerable to heat compared with the non‐pregnant since their basal metabolic rate increases by 20–30% to meet the energy requirements of fetal rapid growth and development (Lof et al ., 2005; Strand et al ., 2011). Previous studies have revealed that high ambient temperature adversely impacts both maternal metabolism and offspring development, including pregnant complications such as preeclampsia and eclampsia (Beltran et al ., 2014; Nasiri et al ., 2014), as well as preterm birth, miscarriage, low birthweight and even teratogenesis (Strand et al ., 2011; Kilinc et al ., 2016; Basu et al ., 2017; Zhang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%